ANALISIS KELAYAKAN USAHA BUDIDAYA BAWANG MERAH PADA KELOMPOK TANI TUNAS HARAPAN DI DESA LUBUK LEBAN KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU - Ahmad Johan Mushoddiq; Sally Maria Bramana; Evi Komalasari (STIE DWI SAKTI BATURAJA, 2021)
This study discusses the feasibility analysis of shallot cultivation in the Tunas Harapan farmer group in Lubuk Leban Village, Sosoh Buay Rayap District, Ogan Komering Ulu Regency. From the research results based on the investment criteria Net Present Value (NPV) Rp. 2,146,873,455 means that the shallot cultivation business is feasible to be implemented. Internal Rate of Return (IRR), 90.45% means that the shallot cultivation business is feasible to be implemented. Profitability Ratio (PR), 49.87 means that shallot cultivation business is feasible to be implemented. Pay Back Period (PBP), 4 months 10 days years means that the shallot cultivation business is feasible to be implemented.